Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(x - 5)2 = 16
=> (x - 5)2 = 42
=> \(\orbr{\begin{cases}x-5=4\\x-5=-4\end{cases}}\)
=> \(\orbr{\begin{cases}x=9\\x=1\end{cases}}\)
(2x - 1)3 = -64
=> (2x - 1)3 = -43
=> 2x - 1 = -4
=> 2x = -4 + 1
=> 2x = -3
=> x = -3/2
( x - 5)2 = 16
=> (x - 5)2 = 42
=> \(\orbr{\begin{cases}x-5=4\\x-5=-4\end{cases}}\)
=> \(\orbr{\begin{cases}x=9\\x=1\end{cases}}\)
a, (\(\frac{1}{2}\))x = \(\frac{1}{64}\)
<=> (\(\frac{1}{2}\))x = (\(\frac{1}{2}\))6
<=> x = 6
b, 35 :3x = 9
<=> 35 :3x = 32
<=> 3x = 35 :32
<=> 3x = 33
<=> x = 3
Chúc bạn học tốt
\(\left(x+2\right)^2=64\)
\(\Rightarrow\left[{}\begin{matrix}x+2=8\\x+2=-8\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x+6\\x=-10\end{matrix}\right.\)
\(\left(x+2\right)^2=64\)
\(\Rightarrow\left[{}\begin{matrix}x+2=8\\x+2=-8\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=6\\x=-10\end{matrix}\right.\)
64:2x=2
⇒ 26:2x=2
⇒ 26-x=21
⇒ 6-x=1
⇒ x=6-1
⇒ x=5
5